UJI SKEMA POLICYHOLDERS BAIL OUT TERHADAP PERUSAHAAN ASURANSI YANG BERMASALAH - Alexander Zaldy Nugraha, Alexander Zaldy Nugraha (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2024)
An Insurance Company is a corporation with a program that offers an agreement between the insurance company and the customer which is useful for helping someone anticipate or minimize the customer's finances when a life risk occurs which can occur at any time, and direct reporting by the Financial Services Authority (OJK) , therefore there is a financial restructuring plan, namely PolicyHolders Bail Out, which is recommended by the OJK for PT. Indosurya Life. The research method used is normative juridical, namely research carried out by referring to legal norms by researching library materials or secondary materials. The research results obtained in this research are that the Policyholders Bail Out scheme has not been regulated in Law no. 14 of 2014 concerning insurance, but this scheme was almost tried by the Indosurya Life company in the context of the insurance company's Financial Restructuring Plan but failed so that the OJK revoked PT's business license. Indosurya Life for the sake of consistency in implementing regulations and protecting the interests of policy holders.